Perceptions of an Air Campaign: the 1991 Persian Gulf War as portrayed by major American print media sources - Padavich, Andrew J (Kansas State University, 2007)
On 16 January 1991, a coalition of nations led by the United States launched a series of air strikes against Iraq to force that country to withdraw from Kuwait. What followed was an intense aerial bombardment of Iraqi military and civilian infrastructure which lasted until 24 February when the coalition began a ground offensive. After four days of ground fighting Iraq withdrew from Kuwait. American pictorial print media created a historical interpretation of the 1991 Persian Gulf War in the sense that selected images were immediately published to a broad audience and these images provided an acceptable story of the war. Perceptions of an Air Campaign examines the cultural meanings of the air war and how these meanings took shape in the narrative pictorial print media produced. The narrative is intricately related to the legacy of the Vietnam War. For generations, Americans viewed contemporary war, politics, foreign affairs, and culture through their memories of the U.S. defeat in Vietnam. President George H.W. Bush guaranteed the U.S. public that the Gulf War was consciously being constructed to avoid a conflict similar to Vietnam. According to the president, the United States was going to war with enough resources for a swift and decisive victory, thereby avoiding the Vietnam pitfall of an open-ended conflict. Pictorial print media articulated a narrative displaying U.S. military strength and dominance that fulfilled Bush’s promise.
Keywords: 1991 Persian Gulf War; Anthropology, Cultural (0326); History, General (0578); History, United States (0337); Journalism (0391); Mass Communications (0708)